Present and future role of grasslands and fodder crops in inter-tropical countries with special reference to over-production and environment - Tothill, J.C.; Dzowela, B.H.; Diallo, A.K. (French Grassland Society, 1990)
Outlines the evolution of man's utilization of the natural and derived grasslands of the intertropical zone in terms of his management of wild and domesticated herbivores; assesses their roles as a primary feed resources for livestock and as an effective means of maintaining soil fertility in the different farming systems of the tropics; and examines the significant socioeconomic constraints on the role of the grasslands.